INTEGRATED CSR TO STRENGTHEN INVESTMENT EFFICIENCY AMID COVID-19: IS IT SUCCESSFUL? - Norsita, Mega; Anjelina , Dayang Anna (JRAK, 2024)
This article contributed theoretically as the first research to look at the impact of CSR performance and investment efficiency on the role of business strategy in developing countries, especially the Southeast Asia Region during the period when COVID-19 and post-COVID-19 pandemics occurred. The primary issue of this research was to assess how the COVID-19 pandemic affected the investment activities of companies in developing nations within the Southeast Asia Region, which was geographically close to China where the COVID-19 outbreak originated. This quantitative research used unbalanced panel data from 210 non-financial enterprises with 381 observations. This research resulting the acceptance of all hypotheses, while CSR performance reduced underinvestment by minimizing information asymmetry, the Prospector strategy increased underinvestment, whereas the Defender strategy did the opposite. This research found that both the Prospector and Defender strategies had a pseudo-moderating impact on CSR performance and investment efficiency amid the COVID-19 pandemic.